The Construction Challenges of Uhuru II Wagon Vessel by Local Engineers under Expatriate Training and Supervision in the Lake Victoria Basin Kisumu, Kenya - (:unkn) unknown (My University, 2023)
The MV Uhuru II is a cargo ship designed to transport cargo within Lake Victoria. It is a powerful and reliable vessel, equipped with a range of sophisticated systems that are essential for its safe and efficient operation. MV Uhuru I and her sister ship MV Umoja were built in 1965 by Yarrow Shipbuilders in Scotstoun, Glasgow, Scotland, and entered service in 1967. At over 300 ft (91 m), they were the longest vessels on any of the East African lakes. The two vessels were owned and operated by the East African Railways and Harbors Corporation (EARH) until 1977, when EARH was divided between Kenya, Tanzania and Uganda. This research paper aims to explore the challenges encountered during the construction of the first vessel in the Lake Victoria Basin by local Engineers. The study provides insights into the various obstacles faced by researchers, engineers, and stakeholders involved in the project by identifying and analyzing these challenges. This paper seeks to contribute to future vessel construction efforts in the region. Local shipbuilding industry seeks to harness the potential of the oceans, lakes and coastal areas while ensuring their long-term health and productivity for future generations. It is estimated that the blue economy, if used properly, has the potential to inject up to 4.8 billion US dollars to Kenya's economy and create over 52,000 jobs in the next 10 years. This, combined with a sustainable approach, should make a difference in the protection of maritime ecosystems. The Lake Victoria Basin is a significant water body in East Africa, providing a vital transportation route and supporting various economic activities; ensuring the long-term viability of fish stocks by implementing effective management practices, combating illegal fishing, and promoting sustainable fishing methods, expanding and promoting responsible aquaculture practices to meet the growing demand for seafood while minimizing environmental impacts. Enhancing port infrast
Keywords: African Research